2003
DOI: 10.1074/jbc.m213037200
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Regulatory Factor-2 Regulates Cell Growth through Its Acetylation

Abstract: We have previously shown that interferon regulatory factor-2 (IRF-2) is acetylated by p300 and PCAF in vivo and in vitro. In this study we identified, by mass spectrometry, two lysine residues in the DNA binding domain (DBD), Lys-75 and Lys-78, to be the major acetylation sites in IRF-2. Although acetylation of IRF-2 did not alter DNA binding activity in vitro, mutation of Lys-75 diminished the IRF-2-dependent activation of histone H4 promoter activity. Acetylation of IRF-2 and IRF-2-stimulated H4 promoter act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 56 publications
2
56
1
Order By: Relevance
“…Although previous studies have indicated that several IRF family members are acetylated and that acetylation inhibits their ability to bind DNA (21,22), our results do not support the notion that treatment of cells with TSA affects the ability of IRF9 to form an ISRE-binding complex with tyrosine-phosphorylated Stat1 and Stat2 (see Fig. 1).…”
Section: Resultscontrasting
confidence: 56%
“…Although previous studies have indicated that several IRF family members are acetylated and that acetylation inhibits their ability to bind DNA (21,22), our results do not support the notion that treatment of cells with TSA affects the ability of IRF9 to form an ISRE-binding complex with tyrosine-phosphorylated Stat1 and Stat2 (see Fig. 1).…”
Section: Resultscontrasting
confidence: 56%
“…Acetylation of IRF-2 leads to inhibition of histone acetylation by p300 in vitro, suggesting a possible mechanism for transcriptional repression by IRF-2 in U937 cells (Masumi and Ozato, 2001). In contrast, we demonstrated that acetylation of IRF-2 regulates cell growth by activation of the H4 promoter (Masumi et al, 2003). In NIH3T3 cells, IRF-2 associates with endogenous p300 and becomes acetylated, binds to an ISRE site, and activates H4 promoter activity.…”
Section: Introductionmentioning
confidence: 66%
“…Interferon regulatory factor-2 recruits nucleolin in the presence of p300/CBP-associated factor Our previous report suggested that it is the involvement of cellular proteins associated with acetylated IRF-2, which results in its transcriptional regulation (Masumi et al, 2003). To identify those proteins that associate with acetylated IRF-2, we performed an M2-agarose pull-down assay using 293T cells transfected with flag-IRF-2 and flag-PCAF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Indeed, several of the nuclear factors that are known to bind to the BLV LTR have been shown to interact with HATs (CREB/ATF, PU.1/Spi-B, USF2, the glucocorticoid receptor, IRF1, and IRF2) (14 -23) and/or with HDACs (rat CREB-1, PU.1, glucocorticoid receptor) (24 -26), and/or to be directly acetylated (rat CREB-1, human CREB-2, IRF2) (21,(27)(28)(29). Among these factors binding to the BLV LTR, the members of CREB/ATF family are of particular interest because they have been demonstrated to play a critical role in BLV gene expression and because they are known to interact with the transcriptional coactivators CBP/p300.…”
mentioning
confidence: 99%